Identification of the effectiveness of higher education marketing strategies using social media - Sintani, Lelo; Fransisca, Yuniati; Anjarini, Ary Dwi; Mulyapradana, Aria (International research journal of management, IT and social sciences, 2021)
There are many ways that universities can promote their programs and services to get the attention of prospective buyers. One strategy is to use social media to promote its products and services. Furthermore, the author believes that the successful promotion of various products owned by investment will determine the University’s progress. We obtained data from publications such as comma books, journals, and several websites discussing university marketing promotion issues on social media pages to fill out this discussion. To answer this royal question, we have to go through the data analysis process by following the rules of scientific studies, including through a coding data evaluation system and drawing conclusions considering that the data we present is valid and reliable. Finally, we can conclude after reviewing the data and also in-depth discussions where we found that the effectiveness of marketing through social media for investment products and services is very appropriate and effective considering that today social media has become a place not only for young people to be friends but also a place for young people to become friends, and literature for business purposes as well as promotion including promotion of high change programs.